Optimalisasi Keterampilan Praktis Petani melalui Program Pendidikan Vokasional Agribisnis di Daerah Gedong Tataan - Oktaria, Vina; Ayu Dian Pratiwi Permatahati; Aan Budianto; Tika Dewi (Wisanggeni: Jurnal Pengabdian Masyarakat, 2021)
This study aims to examine the effectiveness of the agribusiness vocational education program in optimizing the practical skills of farmers in Gedong Tataan, Pesawaran Regency, in 2021. The research employs a qualitative descriptive approach with data collection techniques including in-depth interviews, participatory observation, and documentation. The research subjects consist of farmer trainees, facilitators, and program organizers. The findings indicate that the vocational education program significantly enhanced farmers’ skills, particularly in cultivation techniques, organic fertilizer production, post-harvest handling, and product marketing. The study also reveals that the practice-based learning method (learning by doing) is highly effective in building farmers’ capacity. However, challenges remain, such as limited facilities, low digital literacy, and a lack of post-training assistance. Therefore, the sustainability of the program and multi-stakeholder support are crucial for the development of local agribusiness. This study recommends strengthening the contextual vocational curriculum and integrating technology into future farmer training programs. Keywords: vocational education, farmer skills, agribusiness, training, Gedong Tataan.